Implementation of Sanctions for Violators of the Coronavirus Disease 2019 Community Activity Restrictions - hari, Ju; Dewi, Sumartini; tubi, Kas (CV. Inara, 2022)
Restriction of Community Activities is an effort made by the Government to limit activities carried out by the community in interacting with other citizens, to prevent the possible spread of coronavirus disease 2O19 (COVID-19) outbreak that uses public spaces, public transportation modes, and public buildings. Restriction of Community Activities is carried out with several supervision and enforcement activities. The research method used to compile this scientific work uses normative juridical research, namely by analyzing secondary data in the form of legal materials, especially primary legal materials and secondary legal materials, by understanding the law as a set of favorable rules or norms in the system of legislation governing human life. Violations committed by the community whether it is necessary to apply criminal sanctions for Perpetrators of Violations of Community Activity Restrictions, this certainly needs attention from the government and the need for equal perceptions about the application of criminal acts for perpetrators of violations of community activity restrictions and standards of prosecution. The function of sanctions in criminal law is not merely to scare or threaten the violators. However, more than that, the existence of sanctions must also educate and improve the perpetrator. The sanctions can be applied to violators of health protocols, especially for those who do not wear masks and do not heed the advice of physical distancing by being given administrative sanctions in the form of verbal reprimands, social sanctions, administrative sanctions, and fines.